A composite diaphragm for all-vanadium liquid flow battery and a preparation method thereof
By combining a strong interface in the use of the modified molecular sieve in the septum of the entire pyrine stream battery, it solves the problem of micro -transformation that is prone to micro -transformation at high temperature at high temperatures, and significantly improves the stability and service life of the diaphragm.
Patent Information
- Application Number
- CN202411555848.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-04
AI Technical Summary
When used at high temperatures, all vanadium flow battery separators are prone to minor deformation, resulting in reduced stability and shortened service life.
The composite septum containing the Nafion resin solution, the modified molecular sieve, and the functional auxiliary agent is used. During the preparation of the modified molecular sieve, the molecular sieve raw material and the nitrate solution are reacted. The branch reaction forms a modified molecular sieve.
The modified molecular sieve and the Nafion resin form a strong interface binding and network structure to inhibit the bloating effect brought by the infiltration of positive and negative polard ions, improve the stability of the diaphragm at high temperature, and extend the service life.
Smart Images

Figure 4PZJEBIQSBDQUTBHGHDAWU4ELZHELSHXHHIRXSIC
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of all-vanadium liquid flow batteries, and more specifically, to a composite diaphragm for all-vanadium liquid flow batteries and a preparation method thereof. Background Art
[0002] The all-vanadium liquid flow battery is a redox battery with vanadium as the active substance in a circulating flowing liquid state. It is also the most promising large-scale energy storage technology at this stage. It has the advantages of good electrochemical performance, reasonable cost, easy operation, good safety and low pollution.
[0003] The all-vanadium liquid flow battery has a simple structure and is mainly composed of positive and negative electrodes, proton exchange membranes, electrolyte storage systems, pump systems, etc. The proton exchange membrane is also called a diaphragm, which is an ion conductive membrane located in the center of each single cell. It is used to separate the positive and negative electrolytes inside the single cell to prevent the active substances from mixing with each other to produce "liquid bursting" and self-discharge, and allows the selective transfer of specific ions to ensure the conduction of the internal circuit of the battery; and the diaphragm performance of the all-vanadium liquid flow battery will directly affect the efficiency and life of the battery.
[0004] For example, the invention patent application document with patent publication number CN116706113A discloses a method for preparing a low-cost all-vanadium liquid flow battery diaphragm, which comprises dissolving a perfluorosulfonic acid resin in an organic solvent, dissolving under magnetic stirring conditions, and preparing a perfluorosulfonic acid resin solution with a mass percentage of 3% to 25%; ultrasonically treating the perfluorosulfonic acid resin solution to make the perfluorosulfonic acid resin solution evenly dispersed, and removing bubbles and impurities in the solution, and preparing a mixed solution by mixing the perfluorosulfonic acid resin solution with an ethanol alcohol solution; using a casting method, a slurry coating method or a dipping method to cast the mixed solution into a thin film on a smooth glass surface, the film thickness being between 10 μm and 250 μm, forming a thin film after the solvent evaporates, and peeling the film from the glass surface and drying it, thereby obtaining a diaphragm for an all-vanadium liquid flow battery.
[0005] Regarding the above-mentioned related technologies, the inventors believe that the diaphragm structure obtained by using fluorine-containing resin only by removing bubbles and impurities in the solution cannot meet the application stability requirements under high temperature. Because the sizes of positive and negative ions in the all-vanadium liquid flow battery are different, the osmotic pressures of the positive and negative electrodes are different. At high temperatures, the ion movement speed is faster, the osmotic pressure imbalance is more serious, and at the same time, the swelling of the diaphragm material is aggravated. At this time, the diaphragm is prone to micro-deformation, and it is difficult to exert its excellent and stable effect, and the overall service life is greatly reduced.
[0006] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the invention
[0007] In order to improve the stability of the diaphragm of an all-vanadium redox flow battery in high-temperature applications, the present application provides a composite diaphragm for an all-vanadium redox flow battery and a preparation method thereof.
[0008] In the first aspect, the present application provides a composite diaphragm for an all-vanadium liquid flow battery, which adopts the following technical solution:
[0009] A composite diaphragm for an all-vanadium liquid flow battery is made of the following raw materials in parts by weight:
[0010] 0.5-5 parts of Nafion resin solution;
[0011] Solvent 9-11 points;
[0012] Modified molecular sieve material 0.04-3 parts;
[0013] The modified molecular sieve material is obtained by modifying the molecular sieve raw material through the following steps:
[0014] S1, taking a molecular sieve raw material and placing it in a 0.1 mol / L cerium nitrate solution, stirring and reacting at 75-85°C for 20-24h, filtering, washing, drying, and then calcining to obtain a pretreated molecular sieve raw material;
[0015] S2, placing the pretreated molecular sieve raw material obtained in step S1 in a mixed solution of anhydrous ethanol and water for ultrasonic dispersion, then adding a silane coupling agent, ultrasonically reacting at 75-80° C. for 8-10 hours, and then evaporating to remove the solvent to obtain an intermediate product raw material;
[0016] S3, mixing the intermediate product obtained in step S2 with hydrogen-containing silicone oil, adding a platinum catalyst and heating to 95-105° C., reacting for 2.5-3.5 hours and then cooling, filtering the obtained precipitate, washing it with acetone and then drying it to obtain a modified molecular sieve material.
[0017] By adopting the above technical scheme, Nafion resin solution is a perfluorosulfonic acid polymer solution, which has good thermal stability, chemical stability and electrochemical stability, can provide stable ion transmission channels and efficient power conversion, and can be used to prepare proton exchange membranes; molecular sieve, as a microporous aluminosilicate, has an ordered microporous structure, which can not only reduce the permeability of vanadium ions, but also significantly improve the electrochemical performance of the battery installed in the diaphragm; and using Nafion resin solution and molecular sieve as the main raw materials for the composite diaphragm for all-vanadium liquid flow batteries, the obtained composite diaphragm for all-vanadium liquid flow batteries can play an excellent corresponding role in the application process.
[0018] At the same time, the molecular sieve used in this application is a modified molecular sieve material. In the preparation of the modified molecular sieve material, the molecular sieve raw material is first reacted with a cerium nitrate solution and then calcined to allow cerium to be loaded on the molecular sieve raw material, followed by surface treatment with a silane coupling agent. After introducing chemical bonds on the surface of the pretreated molecular sieve raw material, the hydrogen-containing silicone oil is finally grafted on the molecular sieve surface by a silane addition reaction to obtain a modified molecular sieve material. During the application process, the modified molecular sieve material can form a stronger interface bond and network structure effect with the Nafion resin molecules by means of the grafted material on the surface, and the presence of cerium can inhibit the swelling effect caused by the penetration and shuttling of positive and negative ions. The compounding of the two can bring excellent complementary and adaptive regulation, so that the obtained all-vanadium liquid flow battery diaphragm is not easy to deform when used at high temperature, and can play its own role more stably, and has a longer service life as a whole.
[0019] Preferably, in step S1, the solid-liquid mixing ratio of the molecular sieve raw material and 0.1 mol / L cerium nitrate solution is 1 g: (40-60) mL.
[0020] By adopting the above technical scheme, after the molecular sieve raw material and the cerium nitrate solution in the above mixing ratio react, the pretreated molecular sieve raw material obtained by calcination has a relatively uniform distribution of cerium on its surface, can better cope with the influence of high temperature and give full play to its excellent role, and leaves a relatively suitable area space for the subsequent treatment of silane coupling agent and the grafting of hydrogen-containing silicone oil, thereby ensuring that when the modified molecular sieve material is used, the cerium and the grafted material on its surface can fully cooperate and play a corresponding role, so that the application effect of the modified molecular sieve material is better.
[0021] Preferably, in step S3, the solid-liquid mixing ratio of the intermediate product raw material and the hydrogen-containing silicone oil is 1 g: (15-25) mL.
[0022] By adopting the above technical scheme, the intermediate product raw materials of the above mixing ratio and the hydrogen-containing silicone oil can form a relatively complete graft coating after interaction, so that the obtained modified molecular sieve material has a relatively excellent bonding performance with the Nafion resin molecules, and can maintain a relatively stable application effect when used at high temperatures.
[0023] Preferably, 0.1-0.3 parts by weight of a functional additive is added to the raw material, wherein the functional additive is obtained by calcining zirconium dioxide nanotubes, molybdenum powder and boron powder, and the weight ratio of zirconium dioxide nanotubes, molybdenum powder and boron powder is (5-8):1:(1.4-1.9).
[0024] By adopting the above technical scheme, zirconium dioxide nanotubes can improve the stability of the composite diaphragm for all-vanadium liquid flow batteries at high temperatures. When molybdenum powder, boron powder and zirconium dioxide nanotubes are calcined to obtain functional additives, the synergistic effect of molybdenum and boron can not only strengthen the interface bonding of zirconium dioxide nanotubes and bring about further improvement of high temperature resistance, but also optimize the conductivity. During the application process, it shows a strong inhibitory effect on the unbalanced penetration of positive and negative electrode ions, and can effectively overcome the micro-deformation caused by the increased internal swelling, which is beneficial to further improve the stability of the all-vanadium liquid flow battery diaphragm in high temperature applications.
[0025] Preferably, the weight ratio of the zirconium dioxide nanotubes, molybdenum powder and boron powder is 7:1:1.6.
[0026] By adopting the above technical scheme, after the zirconium dioxide nanotubes, molybdenum powder and boron powder in the above weight ratio are mixed and calcined, the modification effect of the molybdenum powder and boron powder on the surface of the zirconium dioxide nanotubes is relatively uniform, and the effect brought by the combination is more significant, so that the obtained functional additives have a better effect on improving the application stability of the all-vanadium liquid flow battery membrane at high temperature after application.
[0027] Preferably, the molecular sieve raw material is obtained by mixing SAPO-11 molecular sieve and ZMS-5 molecular sieve, and the weight ratio of SAPO-11 molecular sieve to ZMS-5 molecular sieve is 1:(0.3-0.7).
[0028] By adopting the above technical scheme, SAPO-11 molecular sieve is a molecular sieve with specific pore structure and chemical properties, which combines the structural stability of AlPO molecular sieve and the acidic pore structure with cation exchange capacity, and has excellent shape selectivity, thermal stability and hygrothermal stability; ZMS-5 molecular sieve has excellent thermal stability, acid resistance, water vapor stability and hydrophobicity, which enable it to remain stable in high temperature, acidic environment and the presence of moisture; and when SAPO-11 molecular sieve and ZMS-5 molecular sieve are used as molecular sieve raw materials in a specific weight ratio range, they can play a better complementary role, which can not only improve the sample selectivity of all-vanadium liquid flow battery diaphragm, but also improve the vanadium resistance of all-vanadium liquid flow battery diaphragm; at the same time, the molecular sieve raw material obtained by the above combination is also more suitable for modification needs, so that the modified molecular sieve material obtained can play an excellent and stable application effect.
[0029] Preferably, the weight ratio of the SAPO-11 molecular sieve to the ZMS-5 molecular sieve is 2:1.
[0030] By adopting the above technical scheme, when the SAPO-11 molecular sieve and the ZMS-5 molecular sieve in the above weight ratio are mixed as molecular sieve raw materials, the modified molecular sieve material obtained by modification has better application effect, so that the application stability of the all-vanadium liquid flow battery membrane at high temperature is relatively excellent.
[0031] Preferably, the particle size of the molecular sieve raw material is 50-100 nm.
[0032] By adopting the above technical solution, the particle size of the molecular sieve determines the size of the ions it can allow to pass through, and the particle size of the molecular sieve will also affect the ionic conductivity of the diaphragm. The particle size of the above molecular sieve raw material is selected so that the modified molecular sieve material obtained after modification can ensure that the final all-vanadium liquid flow battery diaphragm has excellent application performance after application.
[0033] Preferably, the solvent is one or a combination of ethylene glycol monomethyl ether, dimethyl sulfoxide, dimethylformamide, dimethylacetamide and N-methylpyrrolidone.
[0034] By adopting the above technical scheme, the above types of solvents are all suitable for the preparation of all-vanadium liquid flow battery diaphragms. During the application process, the various component raw materials can be fully mixed and interact with each other, and can also help form a uniform and continuous diaphragm in the film forming process. The film formation quality is high, thereby ensuring that the final all-vanadium liquid flow battery diaphragm has excellent quality.
[0035] In a second aspect, the present application provides a method for preparing a composite diaphragm for an all-vanadium liquid flow battery, using the following technical solution:
[0036] A method for preparing a composite diaphragm for an all-vanadium liquid flow battery comprises the following steps:
[0037] (1) preparing raw materials including Nafion resin solution, solvent and modified molecular sieve material according to the ratio;
[0038] (2) mixing the solvent and the modified molecular sieve material in step (1) and performing ultrasonic dispersion treatment, then adding the Nafion resin solution during the ultrasonic dispersion treatment and mixing them evenly to obtain a composite diaphragm slurry;
[0039] (3) The composite diaphragm slurry obtained in step (2) is coated on a bottom plate and dried to form a film, thereby obtaining a composite diaphragm for an all-vanadium redox flow battery.
[0040] By adopting the above technical scheme, the above steps are simple to operate, and the raw materials are mixed in steps, which is more conducive to quality control in the process. It is not only suitable for large-scale industrial production, but also can obtain a composite diaphragm for all-vanadium liquid flow batteries with excellent and stable quality.
[0041] In summary, this application has the following beneficial effects:
[0042] 1. The modified molecular sieve material can not only form a stronger interface bonding and network structure effect with Nafion resin molecules, but also inhibit the swelling effect caused by the permeation and shuttling of positive and negative electrode ions, so that the obtained all-vanadium liquid flow battery diaphragm is not prone to micro-deformation when used at high temperature, and can exert excellent and stable application effects;
[0043] 2. When the functional additives are obtained by calcining molybdenum powder, boron powder and zirconium dioxide nanotubes in the present application, they can have better interface bonding with other raw materials. While improving the high temperature resistance, they also show a strong inhibitory effect on the imbalanced penetration of positive and negative electrode ions, and can effectively overcome the micro-deformation caused by the increased swelling inside, which is beneficial to further improve the stability of the all-vanadium liquid flow battery membrane in high temperature applications. DETAILED DESCRIPTION
[0044] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.
[0045] Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples of the present application are commercially available:
[0046] Nafion resin solution was purchased from Shanghai Chuangsai Technology Co., Ltd., catalog number PA70011;
[0047] SAPO-11 molecular sieve was purchased from Aos Catalytic Materials (Dalian) Co., Ltd.;
[0048] ZMS-5 molecular sieve was purchased from Shanghai Jiuzhou Chemical Co., Ltd.;
[0049] The silane coupling agent is KH-560 type silane coupling agent;
[0050] Hydrogenated silicone oil was purchased from Jinan Yingyu Chemical Co., Ltd., model 202, industrial grade;
[0051] The platinum catalyst was purchased from Hubei Shineng Chemical Technology Co., Ltd., with an effective platinum content of 2000 PPM;
[0052] The average diameter of the zirconium dioxide nanotubes is 20 nm, the length is 5 μm, and the specific surface area is 30 m 2 / g.
[0053] Preparation examples of raw materials and / or intermediates
[0054] Preparation Example 1
[0055] A modified molecular sieve material is obtained by modifying a molecular sieve raw material through the following steps:
[0056] S1, taking the molecular sieve raw material and placing it in a 0.1 mol / L cerium nitrate solution, stirring and reacting at 80°C for 22 hours, filtering, washing, drying, and then calcining at 500°C for 3 hours to obtain a pretreated molecular sieve raw material;
[0057] S2, placing the pretreated molecular sieve raw material obtained in step S1 in a mixed solution of anhydrous ethanol and water for ultrasonic dispersion, then adding a silane coupling agent, ultrasonically reacting at 77.5° C. for 9 hours, and then evaporating to remove the solvent to obtain an intermediate product raw material;
[0058] S3, mixing the intermediate product raw material obtained in step S2 with hydrogen-containing silicone oil, adding a platinum catalyst and heating to 100° C., reacting for 3.0 hours and then cooling, filtering the obtained precipitate, washing with acetone and then drying to obtain a modified molecular sieve material.
[0059] Note: In step S1, the solid-liquid mixing ratio of the molecular sieve raw material and 0.1 mol / L cerium nitrate solution is 1 g:50 mL; in step S2, the mixing weight ratio of anhydrous ethanol and water is 10:1, the amount of silane coupling agent is 2.5% of the weight of the pretreated molecular sieve raw material, and the ultrasonic power is 300 W; in step S3, the solid-liquid mixing ratio of the intermediate product raw material and hydrogen-containing silicone oil is 1 g:20 mL, and the amount of platinum catalyst is 1% of the weight of the intermediate product raw material; the molecular sieve raw material is obtained by mixing SAPO-11 molecular sieve and ZMS-5 molecular sieve in a weight ratio of 1:0.5, and the particle size of the molecular sieve raw material is 75 nm.
[0060] Preparation Example 2
[0061] A modified molecular sieve material, which is different from Preparation Example 1 in that it is obtained by modifying the molecular sieve raw material through the following steps:
[0062] S1, taking the molecular sieve raw material and placing it in a 0.1 mol / L cerium nitrate solution, stirring and reacting at 75°C for 24 hours, filtering, washing, drying, and then calcining at 500°C for 3 hours to obtain a pretreated molecular sieve raw material;
[0063] S2, placing the pretreated molecular sieve raw material obtained in step S1 in a mixed solution of anhydrous ethanol and water for ultrasonic dispersion, then adding a silane coupling agent, ultrasonically reacting at 75° C. for 10 hours, and then evaporating to remove the solvent to obtain an intermediate product raw material;
[0064] S3, mixing the intermediate product raw material obtained in step S2 with hydrogen-containing silicone oil, adding a platinum catalyst and heating to 95° C., reacting for 3.5 hours and then cooling, filtering the obtained precipitate, washing with acetone and then drying to obtain a modified molecular sieve material.
[0065] Preparation Example 3
[0066] A modified molecular sieve material, which is different from Preparation Example 1 in that it is obtained by modifying the molecular sieve raw material through the following steps:
[0067] S1, taking the molecular sieve raw material and placing it in a 0.1 mol / L cerium nitrate solution, stirring and reacting at 85°C for 20 hours, filtering, washing, drying, and then calcining at 500°C for 3 hours to obtain a pretreated molecular sieve raw material;
[0068] S2, placing the pretreated molecular sieve raw material obtained in step S1 in a mixed solution of anhydrous ethanol and water for ultrasonic dispersion, then adding a silane coupling agent, ultrasonically reacting at 80° C. for 8 h, and then evaporating to remove the solvent to obtain an intermediate product raw material;
[0069] S3, mixing the intermediate product raw material obtained in step S2 with hydrogen-containing silicone oil, adding a platinum catalyst and heating to 105° C., reacting for 2.5 hours and then cooling, filtering the obtained precipitate, washing with acetone and then drying to obtain a modified molecular sieve material.
[0070] Preparation Example 4
[0071] A modified molecular sieve material is different from Preparation Example 1 in that, in step S1, the solid-liquid mixing ratio of the molecular sieve raw material and 0.1 mol / L cerium nitrate solution is 1 g:40 mL.
[0072] Preparation Example 5
[0073] A modified molecular sieve material is different from Preparation Example 1 in that, in step S1, the solid-liquid mixing ratio of the molecular sieve raw material and 0.1 mol / L cerium nitrate solution is 1 g:60 mL.
[0074] Preparation Example 6
[0075] A modified molecular sieve material is different from Preparation Example 1 in that, in step S3, the solid-liquid mixing ratio of the intermediate product raw material and the hydrogen-containing silicone oil is 1 g:15 mL.
[0076] Preparation Example 7
[0077] A modified molecular sieve material is different from Preparation Example 1 in that, in step S3, the solid-liquid mixing ratio of the intermediate product raw material and the hydrogen-containing silicone oil is 1 g:25 mL.
[0078] Preparation Example 8
[0079] A modified molecular sieve material is different from Preparation Example 1 in that the molecular sieve raw material is obtained by mixing SAPO-11 molecular sieve and ZMS-5 molecular sieve in a weight ratio of 1:0.3.
[0080] Preparation Example 9
[0081] A modified molecular sieve material, which is different from Preparation Example 1 in that the molecular sieve raw material is obtained by mixing SAPO-11 molecular sieve and ZMS-5 molecular sieve in a weight ratio of 1:0.7.
[0082] Preparation Example 10
[0083] A modified molecular sieve material, which is different from Preparation Example 1 in that the particle size of the molecular sieve raw material is 50 nm.
[0084] Preparation Example 11
[0085] A modified molecular sieve material, which is different from Preparation Example 1 in that the particle size of the molecular sieve raw material is 100 nm.
[0086] Preparation Example 12
[0087] A modified molecular sieve material, which is different from Preparation Example 1 in that the molecular sieve raw material is SAPO-11 type molecular sieve.
[0088] Preparation Example 13
[0089] A modified molecular sieve material, which is different from Preparation Example 1 in that the molecular sieve raw material is a ZMS-5 molecular sieve.
[0090] Preparation Example 14
[0091] A modified molecular sieve material, which is different from Preparation Example 1 in that it is obtained by modifying the molecular sieve raw material through the following steps:
[0092] S1. Place the molecular sieve raw material in a 0.1 mol / L cerium nitrate solution, stir and react at 80°C for 22 hours, filter, wash with water, dry, and then calcine at 500°C for 3 hours to obtain a modified molecular sieve material.
[0093] Preparation Example 15
[0094] A modified molecular sieve material, which is different from Preparation Example 1 in that the pretreated molecular sieve raw material is replaced with the molecular sieve raw material, and is modified by the following steps:
[0095] S1. Place the molecular sieve raw material in a mixed solution of anhydrous ethanol and water for ultrasonic dispersion, then add a silane coupling agent, and react with ultrasound at 77.5° C. for 9 hours, followed by evaporation to remove the solvent, to obtain an intermediate product raw material;
[0096] S2, mixing the intermediate product raw material obtained in step S1 with hydrogen-containing silicone oil, adding a platinum catalyst and heating to 100° C., reacting for 3.0 hours and then cooling, filtering the obtained precipitate, washing with acetone and then drying to obtain a modified molecular sieve material.
[0097] Example
[0098] Example 1
[0099] A composite diaphragm for an all-vanadium liquid flow battery, the weight of the raw materials used in its preparation is shown in Table 1, and it is prepared by the following steps:
[0100] (1) preparing raw materials including Nafion resin solution, solvent and modified molecular sieve material according to the ratio;
[0101] (2) The solvent and the modified molecular sieve material in step (1) are mixed and then subjected to ultrasonic dispersion treatment at 40° C. and 400 W for 30 min, and then the Nafion resin solution is added during the ultrasonic dispersion treatment, and the ultrasonic treatment is continued for 60 min. The mixture is mixed to obtain a composite diaphragm slurry;
[0102] (3) The composite diaphragm slurry obtained in step (2) is coated on a glass bottom plate and dried at 110° C. for 16 h to form a film, thereby obtaining a composite diaphragm for an all-vanadium redox flow battery.
[0103] Note: The modified molecular sieve material is obtained from Preparation Example 1, and the solvent is dimethylformamide.
[0104] Example 2-3
[0105] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the weights of the raw materials used in its preparation are shown in Table 1.
[0106] Table 1 Raw materials used in the preparation of Examples 1-3 and their corresponding weights (kg / portion)
[0107]
[0108] Example 4
[0109] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 2.
[0110] Example 5
[0111] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 3.
[0112] Example 6
[0113] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 4.
[0114] Example 7
[0115] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 5.
[0116] Example 8
[0117] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 6.
[0118] Example 9
[0119] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 7.
[0120] Example 10
[0121] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 8.
[0122] Embodiment 11
[0123] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 9.
[0124] Example 12
[0125] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 10.
[0126] Example 13
[0127] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 11.
[0128] Embodiment 14
[0129] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 12.
[0130] Embodiment 15
[0131] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 13.
[0132] Example 16
[0133] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that 0.2 parts by weight of a functional additive is also added to the raw material, the functional additive is obtained by calcining zirconium dioxide nanotubes, molybdenum powder and boron powder at 600°C for 6 hours, and the weight ratio of zirconium dioxide nanotubes, molybdenum powder and boron powder is 7:1:1.6, and the functional additive is added together with the modified molecular sieve material.
[0134] Embodiment 17
[0135] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 16 in that the weight portion of the functional additive added is 0.1 parts.
[0136] Embodiment 18
[0137] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 16 in that the weight portion of the functional additive added is 0.3 parts.
[0138] Embodiment 19
[0139] A composite diaphragm for an all-vanadium liquid flow battery, which differs from Example 16 in that the weight ratio of zirconium dioxide nanotubes, molybdenum powder and boron powder is 6.5:1:1.65.
[0140] Embodiment 20
[0141] A composite diaphragm for an all-vanadium liquid flow battery, which differs from Example 16 in that the weight ratio of zirconium dioxide nanotubes, molybdenum powder and boron powder is 5:1:1.4.
[0142] Embodiment 21
[0143] A composite diaphragm for an all-vanadium liquid flow battery, which differs from Example 16 in that the weight ratio of zirconium dioxide nanotubes, molybdenum powder and boron powder is 8:1:1.9.
[0144] Embodiment 22
[0145] A composite diaphragm for an all-vanadium liquid flow battery, which differs from Example 16 in that molybdenum powder is not used in the raw materials of the functional additive.
[0146] Embodiment 23
[0147] A composite diaphragm for an all-vanadium liquid flow battery, which differs from Example 16 in that boron powder is not used in the raw materials of the functional additive.
[0148] Embodiment 24
[0149] A composite diaphragm for an all-vanadium liquid flow battery, which differs from Example 16 in that the functional additive and other components are replaced by zirconium dioxide nanotubes.
[0150] Comparative Example
[0151] Comparative Example 1
[0152] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 14.
[0153] Comparative Example 2
[0154] A composite diaphragm for an all-vanadium liquid flow battery, which is different from Example 1 in that the modified molecular sieve material is obtained from Preparation Example 15.
[0155] Comparative Example 3
[0156] A composite diaphragm for an all-vanadium liquid flow battery is different from Example 1 in that the mass of the modified molecular sieve material is replaced by the raw material of the molecular sieve material before modification.
[0157] Performance testing
[0158] Test samples: The composite diaphragm for all-vanadium redox flow battery obtained in Examples 1-24 was used as test sample 1-24, and the composite diaphragm for all-vanadium redox flow battery obtained in Comparative Examples 1-3 was used as control sample 1-3.
[0159] Test method: The permeability of vanadium ions directly affects the electrochemical reaction efficiency inside the battery, and thus affects the voltage and energy density of the battery. When the permeability of vanadium ions is high, it is easy to cause serious cross-contamination of vanadium ions, resulting in loss of battery capacity and reduced service life.
[0160] Vanadium ion permeability test method: Cut the diaphragm to be measured to a suitable size, then clamp it between two chambers, add 3 mol / L sulfuric acid solution of magnesium sulfate and 3 mol / L sulfuric acid solution of vanadyl sulfate on both sides of the chamber, then take out the liquid from the magnesium sulfate side at a fixed interval, measure it with a spectrophotometer, and get the corresponding vanadium ion concentration. Plot the concentration against time to get the vanadium ion permeability.
[0161] A 4mm thick carbon felt electrode material was selected as the positive and negative electrodes of the battery, and a 5cm×5cm piece of the prepared composite diaphragm material for the all-vanadium liquid flow battery was cut and placed between the positive and negative electrodes, and the above components were fastened with bolts through the preset holes. The positive electrode electrolyte was a solution containing 0.8mol / LV(IV)+0.8mol / LV(V)+3mol / L H2SO4, and the negative electrode electrolyte was a solution containing 0.8mol / LV(II)+0.8mol / LV(III)+3mol / L H2SO4. A peristaltic pump was used to transport the electrolyte to the battery stack to obtain an all-vanadium liquid flow battery;
[0162] First, the test samples 1-24 and the control samples 1-3 were tested according to the above vanadium ion permeability test method, and the obtained vanadium ion permeability was recorded as the initial value A1;
[0163] Secondly, the above-mentioned all-vanadium liquid flow battery was prepared by using the test samples 1-24 and the control samples 1-3, and then the charge and discharge cycle test was carried out; the charging was carried out in a constant voltage charging mode with a charging voltage of 5V, and the discharging was carried out in a constant current discharge mode with a discharge current of 1000A; the charge and discharge cycle was carried out 50 times in an environment with a temperature of 65°C; then the composite diaphragm of the all-vanadium liquid flow battery was removed to carry out a vanadium ion permeability test, and the vanadium ion permeability obtained at this time was recorded as the terminal value A2;
[0164] Finally, the increase rate of vanadium ion permeability of the composite membrane for all-vanadium liquid flow battery is calculated. The increase rate of vanadium ion permeability = (A2-A1) / A1, which is recorded in Table 2 below.
[0165] Table 2 Test results of test samples 1-24 and control samples 1-3
[0166] sample Increase rate of vanadium ion permeability (%) Test sample 1 4.18 Test sample 2 4.34 Test sample 3 4.26 Test sample 4 4.30 Test sample 5 4.28 Test sample 6 4.22 Test sample 7 4.29 Test sample 8 4.31 Test sample 9 4.25 Test sample 10 4.27 Test sample 11 4.33 Test sample 12 4.24 Test sample 13 4.32 Test sample 14 4.81 Test sample 15 4.76 Test sample 16 2.36 Test sample 17 2.45 Test sample 18 2.41 Test sample 19 2.39 Test sample 20 2.44 Test sample 21 2.43 Test sample 22 3.64 Test sample 23 3.51 Test sample 24 4.07 Control sample 1 8.58 Control sample 2 8.31 Control sample 3 10.72
[0167] It can be seen from the combination of Examples 1-5 and Comparative Examples 1-3 and Table 2 that, through the use of modified molecular sieve materials, it is found that the stability of the obtained all-vanadium liquid flow battery diaphragm when applied at high temperature is significantly improved compared to the molecular sieve raw material before modification, and the increase rate of vanadium ion permeability obtained by testing is significantly better. It is also found that if the molecular sieve raw material is only reacted with cerium nitrate solution and then calcined, or directly surface treated with a silane coupling agent and then reacted with hydrogen-containing silicone oil, the modified molecular sieve material obtained after application, the stability of the all-vanadium liquid flow battery diaphragm in application at high temperature is improved, but the improvement effect is extremely limited, and the sum of the two improvement effects is far less than that of Example 1; it can be seen that the modified molecular sieve material of the present application is obtained by composite modification of the above two treatment processes, both of which are indispensable, and the structure formed on the surface of the molecular sieve raw material has a compound synergistic effect, which can significantly improve the stability of the all-vanadium liquid flow battery diaphragm in application at high temperature.
[0168] It can be seen from Example 1 and Examples 6-9 and Table 2 that in the preparation of the modified molecular sieve material, the solid-liquid mixing ratio of the molecular sieve raw material and 0.1 mol / L cerium nitrate solution is 1 g: (40-60) mL, and the solid-liquid mixing ratio of the intermediate product raw material and the hydrogen-containing silicone oil is 1 g: (15-25) mL, both of which can ensure that the obtained modified molecular sieve material can exert an excellent and stable application effect, so that the stability of the all-vanadium redox flow battery membrane in high temperature applications is better.
[0169] It can be seen from Example 1 and Examples 10-15 and Table 2 that when the molecular sieve raw material is a mixture of SAPO-11 molecular sieve and ZMS-5 molecular sieve in a weight ratio of 1: (0.3-0.7) and the particle size of the molecular sieve raw material is 50-100 nm, the molecular sieve raw materials are suitable for modification, so that the obtained modified molecular sieve material can exert an excellent and stable application effect; and when the SAPO-11 molecular sieve or the ZMS-5 molecular sieve is used alone as a molecular sieve raw material, it is found that after the obtained modified molecular sieve material is used, the stability of the obtained all-vanadium liquid flow battery diaphragm in high temperature application will be significantly reduced, and the increase rate of the vanadium ion permeability obtained by the test will increase, indicating that the SAPO-11 molecular sieve and the ZMS-5 molecular sieve have a complementary synergistic effect.
[0170] In combination with Example 1 and Examples 16-21 and Table 2, it can be seen that when the present application uses functional additives obtained by calcining molybdenum powder, boron powder and zirconium dioxide nanotubes, the increase rate of vanadium ion permeability can be significantly reduced, indicating that the stability of the all-vanadium liquid flow battery membrane in high temperature applications has been further improved; in combination with Examples 22-24 and Table 2, it can be seen that if only any one of molybdenum powder and boron powder is used as a functional additive after calcining with zirconium dioxide nanotubes, although it can bring about an improvement in thermal stability, the improvement effect is limited, and the sum of the improvement effects brought by the application of molybdenum powder and boron powder separately is far less than the excellent effect brought by the combination of the two. It can be seen that the synergistic effect brought by zirconium dioxide nanotubes through molybdenum powder and boron powder has a significant improvement effect on the stability of the all-vanadium liquid flow battery membrane in high temperature applications.
[0171] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A composite diaphragm for an all-vanadium redox flow battery, characterized in that: Made from the following raw materials in parts by weight: 0.5-5 parts of Nafion resin solution; Solvent 9-11 points; Modified molecular sieve material 0.04-3 parts; The modified molecular sieve material is obtained by modifying the molecular sieve raw material through the following steps: S1, taking the molecular sieve raw material and placing it in a 0.1 mol / L cerium nitrate solution, stirring and reacting at 75-85°C for 20-24h, filtering, washing, drying, and then calcining at 500°C for 3h to obtain a pretreated molecular sieve raw material; S2, placing the pretreated molecular sieve raw material obtained in step S1 in a mixed solution of anhydrous ethanol and water for ultrasonic dispersion, then adding a silane coupling agent, ultrasonically reacting at 75-80° C. for 8-10 hours, and then evaporating to remove the solvent to obtain an intermediate product raw material; S3, mixing the intermediate product obtained in step S2 with hydrogen-containing silicone oil, adding a platinum catalyst and heating to 95-105° C., reacting for 2.5-3.5 hours and then cooling, filtering the obtained precipitate, washing it with acetone and then drying it to obtain a modified molecular sieve material.
2. The composite diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: In step S1, the solid-liquid mixing ratio of the molecular sieve raw material and 0.1 mol / L cerium nitrate solution is 1 g: (40-60) mL.
3. The composite diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: In step S3, the solid-liquid mixing ratio of the intermediate product raw material and the hydrogen-containing silicone oil is 1 g: (15-25) mL.
4. The composite diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: The raw material is also added with 0.1-0.3 parts by weight of a functional additive, which is obtained by calcining zirconium dioxide nanotubes, molybdenum powder and boron powder, and the weight ratio of zirconium dioxide nanotubes, molybdenum powder and boron powder is (5-8):1:(1.4-1.9).
5. The composite diaphragm for all-vanadium redox flow battery according to claim 4, characterized in that: The weight ratio of the zirconium dioxide nanotubes, molybdenum powder and boron powder is 7:1:1.
6.
6. The composite diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: The molecular sieve raw material is obtained by mixing SAPO-11 molecular sieve and ZMS-5 molecular sieve, and the weight ratio of SAPO-11 molecular sieve to ZMS-5 molecular sieve is 1:(0.3-0.7).
7. The composite diaphragm for all-vanadium redox flow battery according to claim 6, characterized in that: The weight ratio of the SAPO-11 molecular sieve to the ZMS-5 molecular sieve is 2:
1.
8. The composite diaphragm for all-vanadium redox flow battery according to claim 6, characterized in that: The particle size of the molecular sieve raw material is 50-100 nm.
9. The composite diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: The solvent is one or a combination of ethylene glycol monomethyl ether, dimethyl sulfoxide, dimethylformamide, dimethylacetamide and N-methylpyrrolidone.
10. The method for preparing the composite diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: The following steps are involved: (1) preparing raw materials including Nafion resin solution, solvent and modified molecular sieve material according to the ratio; (2) mixing the solvent and the modified molecular sieve material in step (1) and performing ultrasonic dispersion treatment, then adding the Nafion resin solution during the ultrasonic dispersion treatment and mixing them evenly to obtain a composite diaphragm slurry; (3) The composite diaphragm slurry obtained in step (2) is coated on a bottom plate and dried to form a film, thereby obtaining a composite diaphragm for an all-vanadium redox flow battery.
Citation Information
Patent Citations
Preparation method of low-cost all-vanadium redox flow battery diaphragm
CN116706113A
Composite diaphragm of all-vanadium redox flow battery, preparation method and all-vanadium redox flow battery
CN116936892A
Carbon-silicon composite structures and methods of fabricating thereof
US20240128441A1